Remote sensing-based land degradation assessment to inform sustainable development goal 15.3: a case study in Ghanaian Savannah, West Africa - Mukura, G.J (University of Bergen, 2024)
Land degradation (LD) continues to be a global problem affecting humanity and their livelihoods. Like other African countries, Ghana is one of the countries with elevated levels of LD. However, LD assessments in Ghana have been far and wide and it has not been consistent. There have not been any recent assessments done to inform the SDG indicator 15.3.1 in Ghana. This study therefore focused on the Northern, North East, and Upper East of Ghana and bridged the information gaps on LD. This study was conducted within the three northern regions of Ghana, the Northern Region, the North East, and the Upper East Region. The study methods comprised 250m Modis data and high-resolution remote sensing images in 30m Landsat data and subsequently survey from the International Institute for Tropical Agriculture. Agriculture is the primary economic activity, within these regions. Collected data were handled in R Programming Language 4.3.2. The study found that baselines were 50.16% degraded, 40.43% stable, and 9.11% improvement in the Northern Region, and 57.61% degraded, 35.4% stable, and 6.99% improvement in the North East, and 40.35% degraded, 48.24% stable and 11.41% improvement in Upper East. In the adopted approach the study found that for the Northern 81.19% were stable, 18.506% improved, and 0.29% degraded, in the North East 81.02% were stable and 18.66% degraded and 0.39% improved, and Upper East 80.00% stable, 18.18% degraded and 1.81improving. The earth observation almost unanimously agreed with the survey which saw the overall prevalence of land degradation within the regions was 76.8%. However, the survey data was primarily for two regions. The prevalence of LD was significantly higher in the Northern region (60.7%) than in the Upper East region (48.3%; p = 0.003). Of the types of land degradation, most were as a result of soil erosion by water (78.9%) followed by one-third by biological degradation (33.8%) and one-quarter by physical soil deterioration (24.6%). LD as a result of soil erosion by biological degradation (p = 0.018) was significantly different between the regions of the study with the Northern region having predominant LD by biological degradation (43.1%) compared to the Upper East region (24.3%). Furthermore, compared to the Norther region, the Upper East region (cOR: 3.21, 95% CI: (1.47-7.00); p = 0.003) had a 3-odds increased likelihood of land degradation. Specifically, Bolga district (cOR: 26.00, 95% CI: (2.29-295.64); p = 0.009) within the Upper East region had a 26-odds increased likelihood of land degradation. Causes of land degradation including water, physical soil deterioration, and direct and natural causes of land degradation were significantly different between the regions of the study (p < 0.05). In addition, land degradation as a result of improper soil management is significantly different between the regions of the study (p < 0.05). LD remains high in the Northern, North East and Upper East regions of Ghana. Addressing land degradation requires region-specific tailored interventions to the predominant forms of land degradation and causes in Ghana.